Economic policy and the regulation of corporate securities - Manne, Henry G.; The National Law Center, George Washington University; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1969)
This is the proceedings of a symposium sponsored by the National Law Center [of] George Washington University and American Enterprise Institute for Public Policy Research [in March 1968]. The subject of Securities regulation has been almost the exclusive province of lawyers and law professors from about the time that securities regulation first became recognized as a separate field.
Includes bibliographical references and index.
uaa 24/01/2019
Loans
Keywords: Securities; Stock exchanges; Financial statements